Seed setting, combining ability and heterosis studies in gladiolus (Gladiolus grandiflorus) - Mahato, Suresh K; Gantait, Subhendu S (The Indian Journal of Agricultural Sciences, 2020)
The seed setting, combining ability and heterobeltiosis analysis was carried out in gladiolus (Gladiolus grandiflorus L.) based on 5 × 5 full diallel mating for different traits utilizing five genotypes, viz. ACC-15, ACC-13, ACC-11, ACC-14 and ACC-04 for the experiment. Experimental results revealed that days required for maturity of capsules, harvest percentage of capsule, number of seeds per capsule, hundred seeds weight and seed germination percentage were varied significantly among the crosses. The maximum harvestable capsules was recorded in ACC-13 × ACC- 14 and its reciprocal cross while maximum number of seeds per capsule was found in the cross ACC-15 × ACC-13. The genotypes, viz. ACC-15, ACC-11 and ACC-14 were good general combiners for most characters for many traits. ACC-04 × ACC-14 had the highest SCA effects for diameter of cormel and can be used in both yield and quality improvement. Though, most of crosses showed a negative mid-parent and high-parent heterosis, hybrids expressing the highest MPH and HPH heterosis overall, were ACC-15 × ACC-13, ACC-14 × ACC-15 and ACC-04 × ACC-14.